Analysis of Factors Affecting Success in Accounting Courses: A Study on Students Taking Accounting Courses (Third Sector Social Economic Review, 2025)
In this study, statements pertaining to factors that may influence success in accounting courses were derived from a comprehensive literature review and subsequently transformed into a draft scale. This draft scale comprises a total of 32 statements, 6 of which pertain to demographic characteristics. These statements underwent testing on a sample of 48 students within the framework of a pilot study. Based on the results of the pilot study and the assessment of expert opinions, it was determined that 15 statements were superfluous and were thus excluded from the scale. The revised scale comprises a total of 17 statements, including 6 statements that assess demographic characteristics.The newly developed scale was utilised to assess 504 pupils now enrolled in accounting courses at university situated in seven distinct locations of Turkey as of 2024. The data acquired from the application has undergone many analyses. Based on the conducted analyses, it has been noticed that there are four dimensions that determine success in the accounting course. These dimensions account for 80.096% of the elements that influence success in the accounting course. The completed normality analysis indicates that the data follows a normal distribution. The regression analysis reveals that the eacher explaining the lesson (TEEL) and the student's perception of the lesson (SPL) have a positive and significant impact on success in the accounting course (SAC). Conversely, the variable of environmental effects (EE) has a negative and significant effect on SAC.
Keywords: Accounting; Accounting Course Achievement; Impact Factors; Scale Development; Analysis